Hunger‐dependent and sex‐specific antipredator behaviour of larvae of a size‐dimorphic mosquito. (29th July 2014) - WORMINGTON, JILLIAN D.; JULIANO, STEVEN A.
<x xml:space="preserve">Abstract</x> 1. Modification of behaviours in the presence of predators or predation cues is widespread among animals. The costs of a behavioural change in the presence of predators or predation cues depend on fitness effects of lost feeding opportunities and, especially when organisms are sexually dimorphic in size or timing of maturation, these costs are expected to differ between the sexes. 2. Larval Aedes triseriatus (Say) (Diptera: Culicidae) were used to test the hypothesis that behavioural responses of the sexes to predation cues have been selected differently due to different energy demands. 3. Even in the absence of water‐borne predation cues, hungry females (the larger sex) spent more time browsing than did males, indicating a difference in energy needs. 4. In the presence of predation cues, well‐fed larvae of both sexes reduced their activity more than did hungry larvae, and males shifted away from high‐risk behaviours to a greater degree than did females, providing the first evidence of sex‐specific antipredator behaviour in foraging mosquito larvae. 5. Because sexual size dimorphism is common across taxa, and energetic demands are probably correlated with size dimorphism, this research demonstrates the importance of investigating sex‐specific behaviour and behavioural responses to enemies, and cautions against generalising results between sexes.